Cloud Cover and Uv Index Estimates in Chile from Satellite-Derived and Ground-Based Data - Cordero-Carrasco, R; Damiani, A (2014)
Data of Lambertian equivalent reflectivity (LER) in ultraviolet (UV)-A range recorded by Total Ozone Mapping Spectrometer (TOMS) series aboard Nimbus 7 and Earth Probe and by Ozone Monitoring Instrument (OMI) on EOS Aura have been analyzed over eight Chilean locations spanning from about 18° to 62° S (i.e. including Profesor Julio Escudero station, Antarctic peninsula), covering years 1978-2011. Generally the distribution of the reflectivity is similar for both TOMS datasets. A slightly better agreement has been found for the most southern locations while a small discordance appears for northern locations. The latter could be partly due to actual differences in the cloud cover conditions. On the other hand, OMI LER data differ from TOMS ones in almost all locations. Daily cloud modification factor (CMF) values from ground-based global solar irradiance measurements have been compared with OMI LER-based CMF data. The northernmost and southernmost locations characterized by prevalent clear sky and winter snow conditions, respectively, showed the worse agreement with a correlation coefficient r. = 0.63 and 0.71, while other stations showed a better correlation (i.e. r. =0.83 and r. = 85).Clear sky ground UV index values for Santiago de Chile have been estimated for years 1979-2011 by means of an empirical reconstruction model based on data recorded by a multichannel radiometer. It allowed computing a ground-based CMF for years 1996-2011 and comparing it with satellite data. Results show that OMI CMF based on gridded cell LER data introduces significant differences with respect to equivalent TOMS CMF. On the contrary, the use of overpass LER data allows to evaluate changes in cloudiness and, by using the model, reconstructing the actual UV index. Nevertheless, LER CMF overestimates actual cloud cover conditions in winter. The trend in reconstructed satellite (ground) based UV index during summer months is +. 3.3. ±. 0.9% (+. 11.9. ±. 2.5%)/decade for years 1979-2011 (1997-2011). Further comparisons concerning the Total Cloud Fraction product of Modern-Era Retrospective analysis for Research and Applications (MERRA) suggest that it could be used a further proxy of cloudiness for UV reconstruction models; nevertheless additional analysis is necessary. © 2013 Elsevier B.V.